Better Together: Academic and Industry Collaboration for Experiential Learning - Chan, Ete; Savoca, Marianna; Zalewski, Urszula (Experiential Learning and Teaching in Higher Education, 2025)
Connecting experiential education (EE) and career readiness (CR) is essential for students’ long-term career development. As we envision the future and “SEE the way forward” of making stronger connections between EE & CR, we present this innovative collaborative of faculty, staff, and employers, and present several case examples of different ways we engage employers with EE inside and outside of the classroom. The goal of this conference session was to spark creativity through our examples and give participants time to ideate how they might absorb, tweak, build upon these ideas to work in their unique campus contexts.